2016
DOI: 10.1007/s11908-016-0555-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in Pediatric Urinary Tract Infections

Abstract: Urinary tract infections (UTIs) are a common problem in pediatric patients. Resistance to common antibiotic agents appears to be increasing over time, although resistance rates may vary based on geographic region or country. Prior antibiotic exposure is a pertinent risk factor for acquiring resistant organisms during a first UTI and recurrent UTI. Judicious prescribing of antibiotics for common pediatric conditions is needed to prevent additional resistance from occurring. Complex pediatric patients with histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
3
17
1
3
Order By: Relevance
“…In this study, nearly half of the isolates were resistant to the majority of the tested antimicrobials, with 34.6% of the strains demonstrating MDR, which is in agreement with previous studies conducted in different regions of Turkey 12,24 . In accordance with the results of the study, 67.3%, 50.9%, 45.1%, 45.1%, 38.7%, 36.6%, 35.9%, 35.9%, and 32.7% were resistant to ampicillin, amoxicillin-clavulanic acid, cefazolin, trimethoprimsulfamethoxazole, cefuroxime, ceftriaxone, ciprofloxacin, cefepime, and norfloxacin, respectively, which are the first-line therapeutic agents used for UTI treatment 23,25 . These resistance rates may be explained by the frequent prescription of these antimicrobials in empirical treatment of UTIs.…”
Section: Determination Of Antimicrobial Resistance and Virulencesupporting
confidence: 89%
“…In this study, nearly half of the isolates were resistant to the majority of the tested antimicrobials, with 34.6% of the strains demonstrating MDR, which is in agreement with previous studies conducted in different regions of Turkey 12,24 . In accordance with the results of the study, 67.3%, 50.9%, 45.1%, 45.1%, 38.7%, 36.6%, 35.9%, 35.9%, and 32.7% were resistant to ampicillin, amoxicillin-clavulanic acid, cefazolin, trimethoprimsulfamethoxazole, cefuroxime, ceftriaxone, ciprofloxacin, cefepime, and norfloxacin, respectively, which are the first-line therapeutic agents used for UTI treatment 23,25 . These resistance rates may be explained by the frequent prescription of these antimicrobials in empirical treatment of UTIs.…”
Section: Determination Of Antimicrobial Resistance and Virulencesupporting
confidence: 89%
“…However, compared to previous reports from Nepal, we observed a considerable increase in resistance against penicillins, aminoglycosides, quinolones and ceftriaxone [12, 31]. Lower rates of resistance among the pediatric isolates causing UTI have been documented in western countries [33]. …”
Section: Discussioncontrasting
confidence: 60%
“…12 Lower rates of resistance among the paediatric isolates causing UTI have been documented in western countries. 31 In the present study Klebsiella isolates showed resistance against broad spectrum cephalosporin, macrolides and amoxicillin/clavulanic acid which is consistent with the previous data of other communitybased studies. 32 The most potent drugs were gentamicin, imipenem, nitrofurantoin and levofloxacin.…”
Section: Discussionsupporting
confidence: 93%